The Correlation between Leukocytes and Bacterial Number from Urine of Type 2 Diabetes Mellitus Patients Using Urine Analyzer - Novia Agustina; Diana Pratiwi; Nurul Istiqomah (Indonesian Journal of Pharmaceutical Education, 2023)
Diabetes Mellitus (DM) is a chronic metabolic disorder. DM can occur if the pancreas does not produce enough insulin or the insulin that is produced isnâ€™t effectively used. Patients with diabetes mellitus have a high risk for chronic microvascular complications, including infection. This research aimed to determine the correlation between leukocytes and bacterial number from urine of patients with Type 2 Diabetes Mellitus at the X Hospital Blitar. This research used a cross sectional method, with 47 urine samples of Type 2 Diabetes Mellitus patients by purposive sampling, were tested with urine analyzer. The result showed that the number of high leukocytes was 13 (28%) respondents and normal leukocytes was 34 (72%) respondents. While the number of bacteria from respondentsÂ  was normal 21 (45%) and high number was 26 (55%). Based on the Spearman-rho correlation test on SPSS, it can be concluded that there was a significant relationship between leukocytes with bacterial number of urine from Type 2 Diabetes Mellitus patients, with sig = 0,000 (0,05) and the correlation coefficient = 0,515.